2011
DOI: 10.2174/156720511798192745
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Abilities of Alzheimers Disease Transgenic Mice are Modulated by Social Context and Circadian Rhythm

Abstract: In the present study, we used a new training paradigm in the intelliCage automatic behavioral assessment system to investigate cognitive functions of the transgenic mice harboring London mutation of the human amyloid precursor protein (APP.V717I). Three groups of animals: 5-, 12-and 18-24-month old were subjected to both Water Maze training and the IntelliCage-based appetitive conditioning. The spatial memory deficit was observed in all three groups of transgenic mice in both behavioral paradigms. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…The Morris water maze is one of the behavioral tasks most often used to assess cognitive abilities of mice. In our previous study we observed similar spatial memory deficits in mice tested in the water maze and place preference paradigm in the IntelliCage system (Kiryk et al, 2011). Therefore, we decided to further investigate this relation by measuring LTP in the CA1 field of the hippocampus in C57BL/6 and BALB/c valproate-treated and control mice and assess its correlation with place preference learning in the IntelliCage system.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The Morris water maze is one of the behavioral tasks most often used to assess cognitive abilities of mice. In our previous study we observed similar spatial memory deficits in mice tested in the water maze and place preference paradigm in the IntelliCage system (Kiryk et al, 2011). Therefore, we decided to further investigate this relation by measuring LTP in the CA1 field of the hippocampus in C57BL/6 and BALB/c valproate-treated and control mice and assess its correlation with place preference learning in the IntelliCage system.…”
Section: Discussionsupporting
confidence: 67%
“…The learning chamber with water access was assigned randomly, with no more than 3 mice drinking from the same conditioning unit. Such procedure minimizes social modulation of learning (Kiryk et al, 2011). To increase animals' motivation for visiting the assigned corner, tap water was replaced by 10% sucrose solution (Sigma-Aldrich), which is strongly preferred by both investigated mice strains (Figures 1K,L).…”
Section: Methodsmentioning
confidence: 99%
“…However, in all experiments contributing to the data set analyzed here, experimental groups were mixed in each cage, opening the possibility that interaction between groups in the same cage may have influenced behavioral profiles, for example through competition or imitation. In fact, this has been demonstrated previously for a learning task, in which a transgenic mice harboring the London mutation of the human amyloid precursor protein (APP.V717I) were only impaired when tested in a separate cage, but not when tested together with wild-type controls (Kiryk et al, 2011). Whether social interactions can reduce differences in spontaneous behavior in a similar way is unknown and would need to be tested in a controlled study.…”
Section: Dimensions Of Behavioral Variation During Free Adaptationmentioning
confidence: 75%
“…For instance, co-housing of BL6 and BTBR [a mouse model of autism-like behavior (Moy et al, 2007)] strains has been effective in rescuing the social deficits in the BTBR strain (Yang et al, 2011). Another study has shown a beneficial effect of co-housing the wild type and transgenic mice on learning performance in a model of Alzheimer's disease (Kiryk et al, 2011). Social learning is involved in the transmission of social behaviors, which has been described not only for humans but also for animals.…”
Section: Discussionmentioning
confidence: 99%
“…Re-socialization (group-housing with normally developed peers) rescued the prosocial deficit induced by post-weaning social isolation in rats (Tulogdi et al, 2014). The effectiveness of group-learning and social enrichment in facilitation of learning and memory was also validated in an animal model of Alzheimer's disease (Kiryk et al, 2011) and in BTBR mice (Lipina and Roder, 2013). …”
Section: Introductionmentioning
confidence: 98%